Quasi‐fixed frequency controlled phase modulation LCC resonant converter with a wide power range - Ying Feng; Dejun Kong (IET Circuits, Devices and Systems, 2023)
Abstract The research on LCC resonant converters has become increasingly popular since the application of the zero‐voltage switching can improve the transmission ability and ensure the high efficiency of the power supplies. In this article, a novel quasi‐definite frequency‐based modulation control method to extend the excellent properties of LCC resonators to a wide range of powers is introduced. By adjusting the frequency and phase in a bidirectional manner in accordance with the design law, excellent output performance can be maintained over a wide power range, which is overcome by adjusting the switching frequency and phase separately in conventional modulation methods. In order to justify the effectiveness of the proposed modulation control method, a simulation and experimental platform of LCC resonators using the proposed modulation method was performed. Simulation and experimental results can effectively demonstrate the performance of the proposed modulation control method for a variety of input voltage and output power cases, and the efficiency of the LCC converters will be improved in higher power systems.